TEAR REPLACEMENT COMBINATION DRUGS IN THE TREATMENT OF DRY EYE SYNDROME - A. V. Jani; E. A. Seliverstova (Российский офтальмологический журнал, 2018)
60 outpatients with weak and moderate dry eye syndrome were followed in order to perform a comparative efficiency evaluation of three tear replacement drugs: Stillavit, Vismed and Tears naturale. Changes in the condition of the eye were estimated using biomicroscopy data and diagnostic tests (including Schirmer test, Norn test, Lipkof test, lacrimal meniscus height, and fluorescein eye stain test). The patients were divided into 3 groups, each consisting of 20 patients, who respectively received instillations of two drops of the three drugs, 3 times a day for 40 days. The last examination was given on the 60th day of observation period since the drugs had been discontinued. As a result of treatment, positive changes were observed in all three observation groups. A pronounced improvement was achieved in the condition of the eyelids, conjunctiva and the cornea, as well as in the parameters of the diagnostic tests. In weak dry eye syndrome, full-scale moisturizing and formation of stable tear film is recommended, which is achievable with Vismed 0.18 %. In dry eye syndrome complicated by keratopathy, the therapeutic effect of the tear replacement drug must be strengthened by adding keratoprotectors, which is best achieved by the three-component eye solution, Stillavit. For citation: Jani Е.V., Seliverstova К.Е. Tear replacement combination drugs in the treatment of dry eye syndrome. Russian ophthalmological journal. 2018; 11 (3): 63-9 (In Russian). doi: 10.21516/2072-0076-2018-11-3-63-69.